Changes in Gender Inequality and Intimate Partner Violence From 1958-2003: A Birth Cohort Analysis - Metheny, Nicholas (Violence against women, 2021)
This article uses a birth cohort analysis to examine whether the sociopolitical environments in which a woman forms attitudes around intimate partner violence (IPV) influence report of physical, sexual, and emotional IPV, and IPV justification in 25 low- and middle-income countries. Cohort effect is then examined across countries by rate of decline in gender inequality over time as measured by the Gender Inequality Index (GII). Results suggest a birth cohort effect for all types of IPV, with women reporting greater odds of IPV with each successive cohort. This is reversed when countries are stratified by rate of GII decrease, but wanes as the rate slows.